The Use of Factor Analyses in Validating Filipino Needs Scale in Tertiary Education - elnar, ryan dale bagay (Advances in Social Sciences Research Journal, 2018)
Needs is a psychological construct considered to be one of the facets of personality since need researches has shown its strong potency in predicting behaviors. The present study tested the factor structures of a need measure among Filipino university students purposely for academic and psychological interventions. Employing qualitative analysis to determine need items in the initial study, findings show that the developed factor structures composed of clustered need items is robust to test students’ needs as it attains an excellent overall internal consistency (α=.94). As homogeneity of all measured factors are highly correlated (range: .751-.902), other need constructs (BPNS and EPPS Scales) also reveals strong concurrent validity to the need measure’s factor structures. Series of factor analyses such as the use of exploratory and confirmatory factor analyses exhibits similar structural findings which yielded to a 1–factor-6-higher-order need measure. Moreover, the scale’s fit indices indicated a very good fit model: χ2-df (540.876; 307), GFI (0.800) AGFI (0.889) TLI (0.874) RMSEA (0.072). Research findings were discussed in terms of the scale’s efficacy to diagnose specific academic issues and broadly in indentifying learning gaps of college students in tertiary schools.